Hybrid Approach to Steganography System Based on Quantum Encryption and Chaos Algorithms (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This paper proposes a hybrid system for secretly embedding images into the dithered multilevelimage. Confident hybridizations between steganography and quantum encryptions are either rare inliterature or suffer a poor effectiveness in secure communication. This paper scrambles and divides thesecret image into groups to be embedded in the blocks of the cover image using three chaos algorithms.These are Lorenz map, Henon map, and Logistic map algorithms. The encryption of embedded imagesconducted using the quantum one-time pad. Results showed that the proposed hybrid system succeeded inembedding and combining images with quantum cryptography algorithms.